Two- and three-body abrasive wear behaviour of different heat-treated boron alloyed high chromium cast iron grinding balls - Izciler, M; Çelik, H (Elsevier Science Sa, 2000)
In this study, the abrasive wear performance of different heat-treated boron alloyed high chromium cast iron ore grinding balls was examined. Laboratory tests were carried out using pin-on-disc and rubber wheel abrasive testers. Three different loads (32.3, 53.7 and 83.7 N) were applied for two-body high stress abrasion tests (on pin-on-disc). Low stress abrasion tests were performed with a test duration of 1270 revolutions under a load of 56N on a rubber wheel abrasive tester. Mass loss was measured using a 10(-4) balance. The microstructures of the specimens were examined using both optical and scanning electron microscopes. Carbides and matrix were identified by etching, electron dispersive spectrograph (EDS) and X-ray diffractometer analysis. (C) 2000 Published by Elsevier Science B.V.
Keywords: iron grinding balls; boron alloys; abrasive wear performance